(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the demographic situation and development trends of the population of Khavast District of Syrdarya Region, as well as the districtʼs position within the region based on key demographic indicators using statistical data. The study examines the total population, the distribution of urban and rural residents, the age-sex structure, as well as the natural and mechanical movement of the population on the basis of statistical materials. In addition, the socio-economic factors, migration processes, and population density influencing changes in the population size were analyzed.